Penilaian Green Building Gedung Kuliah B Fakultas Ekonomi dan Bisnis Universitas Lampung Berdasarkan Kriteria Green Building Council Indonesia - Siregar, Amril Ma’ruf; Arifaini, Nur; Ifadianto, Nugroho; Putri, Wanda Noor Amalia (Universitas Ibn Khaldun, 2025)
Lampung University plays an active role in implementing and campaigning for green development, so a study is needed that can be used as part of the implementation of the Green Building concept. The selection of the location of Building B FEB is based on the condition of the building which is still new so that it is expected to be easier to improve. The research method includes a survey of building conditions, interviews, and assessment of six green building criteria based on the Green Building Council Indonesia (GBCI) version 1. These criteria include Appropriate Site Development (ASD), which emphasizes the selection of a location and sustainable management of the surrounding environment; Energy Efficiency and Conservation (EEC), which focuses on reducing energy consumption and implementing energy-saving technologies; Water Conservation (WAC), which highlights the efficiency of water use and management; Material Resource and Cycle (MRC), which refers to the use of environmentally friendly and easily recycled materials; Indoor Health and Comfort (IHC), which includes air quality, lighting, acoustics, and occupant thermal comfort; and Building Environmental Management (BEM), which focuses on sustainable building operations, including waste management and maintenance. The results of the survey and field analysis show that the total Green Building assessment score of Building B FEB Unila is 37, which is in the Bronze category. Efforts that can be made to increase this value include the commitment of the entire academic community in environmental campaigns, reducing the use of private motor vehicles, and water conservation in building management.